2021
DOI: 10.1016/j.ensci.2021.100357
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of structured exercises on motor skills, physical fitness and attention in children with ADHD compared to typically developing children-A pilot study

Abstract: Purpose: Children with ADHD exhibit decrements in fitness levels, motor skill ability and attention. The purpose was to evaluate the benefits of a structured, school-based exercise program on motor skill, physical fitness and attention in children with ADHD. Method: Ten 8–12 year old school boys with ADHD and ten typically developing (TD) were recruited. They underwent a six week structured exercise program which included aerobics, resistance exercises, motor skills and attention training. Results: Following t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Neuro-Linguistic Programming (NLP) is being investigated as a potential technique for improving outcomes for individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) 18 . NLP techniques, such as affirmation, visualization, anchoring, reframing, role-playing, and role modeling, have been studied as a possible brain rewiring technique for individuals with ADHD 18,32,36 . For instance, a case study by Jeyanthi et al showed that a 9-year-old boy with ADHD who participated in an intervention program combining NLP techniques with exercise demonstrated a positive impact on attention and motor skills 32 .…”
Section: Neuro-linguistic Programming (Nlp)mentioning
confidence: 99%
“…Neuro-Linguistic Programming (NLP) is being investigated as a potential technique for improving outcomes for individuals with Attention-Deficit/Hyperactivity Disorder (ADHD) 18 . NLP techniques, such as affirmation, visualization, anchoring, reframing, role-playing, and role modeling, have been studied as a possible brain rewiring technique for individuals with ADHD 18,32,36 . For instance, a case study by Jeyanthi et al showed that a 9-year-old boy with ADHD who participated in an intervention program combining NLP techniques with exercise demonstrated a positive impact on attention and motor skills 32 .…”
Section: Neuro-linguistic Programming (Nlp)mentioning
confidence: 99%